The Effect Of Flexible Working Hours And Compensation On Driver Performance With Job Satisfaction As An Intervening Variable At Pt Gojek Makassar - Muh. Hidayat; Eka Suhartini; Akhmad Jafar (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study aims to analyze the effect of flexible working hours and compensation on the performance of Gojek drivers in Makassar, with job satisfaction as an intervening variable. The background of this study is based on drivers' need for flexibility in working hours to balance the demands of work and personal life, as well as the importance of adequate compensation to increase motivation and loyalty. Research Approach and Location This study uses an associative quantitative approach to identify relationships between variables. The research location is PT Gojek's Makassar branch, focusing on Gojek two-wheeled drivers (GoRide). The sample used consists of 120 Gojek drivers in Makassar, selected using Hair's formula, which was determined using incidental sampling techniques. Data Analysis The data analysis method uses Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. Testing was conducted through convergent validity, discriminant validity, and reliability. The results of the study show that flexible working hours and compensation play an important role in increasing the satisfaction and performance of Gojek drivers in Makassar. Job satisfaction has been proven to be a significant intervening variable, strengthening the relationship between flexible working hours and compensation with performance. These findings underscore the importance of policies that support work-life balance and fair compensation in order to increase the motivation, loyalty, and productivity of Gojek drivers.